The early interaction of Leishmania with macrophages and dendritic cells and its influence on the host immune response - Liu, Dong; UZONNA, JUDE E. (Frontiers in Cellular and Infection Microbiology, 2012)
The complicated interactions between Leishmania and the host antigen-presenting cells (APCs) have fundamental effects on the final outcome of the disease. Two major APCs, macrophages and dendritic cells (DCs), play critical roles in mediating resistance and susceptibility during Leishmania infection. Macrophages are the primary resident cell for Leishmania: they phagocytose and permit parasite proliferation. However, these cells are also the major effector cells to eliminate infection. The effective clearance of parasites by macrophages depends on activation of appropriate immune response, which is usually initiated by DCs. Here, we review the early interaction of APCs with Leishmania parasites and how these interactions profoundly impact on the ensuing adaptive immune response. We also discuss how the current knowledge will allow further refinement of our understanding of the interplay between Leishmania and its hosts that leads to resistance or susceptibility.